Lignocellulosic biomass for bioenergy beyond intensive cropland and forests - Van Meerbeek, Koenraad; Muys, Bart; Hermy, Martin (Renewable & sustainable energy reviews, 2019)
Pathways towards decarbonization of society to limit global warming well below 2 °C heavily rely on bioenergy. The predicted increase in biomass demand raises concerns about the sustainability of large-scale bioenergy deployment. To investigate the diversification of biomass supply this synthesis gives an overview of the underused biomass potential of landscapes beyond croplands and forests: gardens, roadsides, conservation areas, sport fields etc. In Western Europe, their annual biomass production ranges from 2.0 to 9.2 Mg dry matter per hectare, while intensive agriculture can produce 12.0–20.4 Mg dry matter per year under the same climatic conditions. However, the net energy balance (energy output minus energy inputs) of landscape bioenergy has the potential to be higher than that of some of the current bioenergy systems (ranges between 4.9–28.4 and 11.0–68.8 GJ per ha respectively). These landscape elements have in common that biomass is removed for other purposes than bioenergy production and they already provide indispensable ecosystem services to society. The scattered availability of this resource in space and time, however, limits a general implementation of landscape bioenergy. The deployment of landscape biomass is promising in regions where the management is organized, and where it could be combined with the energetic valorization of other organic waste streams. In a case study, the landscape biomass potential of an urbanized region in Western Europe is quantified and the feasibility of integrating landscape biomass together with other waste streams in the bioenergy chain is further explored. Anaerobic digestion of 1087 Gg landscape biomass (fresh weight) together with other organic waste streams could potentially generate 12.7 PJ gross per year, or 20% of the current renewable energy production in the study region. Results of this study show that landscape biomass has the potential to diversify the current biomass portfolio and can effectively contribute to the decarbonization of society. [Display omitted] •Future supply of biomass for bioenergy needs to be diversified.•A global overview of biomass and bioenergy potential in the landscape is provided.•Gardens, urban green, invaded areas, conservation and recreation areas are studied.•Assessment of landscape biomass potential in an urbanized region of Western Europe.•Barriers and recommendations towards deployment of landscape biomass are discussed.